NICU Healthcare Workers Hand Hygiene Compliance during 6 Months of Direct Observation - Inna Fairuuza Firdaus; Dwiyanti Puspitasari; Marijam Purwanta (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Hospitalized neonates are at risk of developing nosocomial sepsis, a systemic infection due to unhygienic healthcare, especially in Indonesia where healthcare-associated infection incidence rate is 5.9%-8.3%. Hand hygiene by healthcare workers is an effective measure to prevent it. This study aimed to understand the healthcare workers’ hand hygiene compliance towards WHO guidelines 2009 in Dr. Soetomo General Hospital NICU. Methods: This research was an observational study. The healthcare workers’ hand hygiene compliance was obtained through 6 months of direct observation, from November 2018 to April 2019, with doctors and nurses who agreed to be observed and present during the observation period as samples. The observation was recorded with WHO observation form, and processed with Microsoft Excel 2013 to obtain compliance rate. Results: Overall, the compliance of healthcare worker in NICU Dr. Soetomo General Hospital during the 6 months of study was 84%. Nurses’ compliance was higher (87%) than doctors’ (78%). Compliance to My 5 Moments of Hand Hygiene indications varied from 82% for moments before patient contact to 93% for moments after patient contact. Conclusion: In conclusion, hand hygiene compliance of healthcare workers in Dr. Soetomo General Hospital NICU varied between profession categories and each indication. To maintain and improve hand hygiene compliance, intervention in healthcare workers’ behavior is needed, so that healthcare-associated infection can be better prevented.